PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS POP UP BOOK PADA PEMBELAJARAN TEMATIK DI KELAS 1 - Iin Kurniawan; Kartono; Dyoty Aulia Vilda Ghasya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to create pop-up book-based learning media that is appropriate for thematic learning in class 1. theme 2. sub-theme 3. The research method used is research and development (R&D) by adapting Borg and Gall's design developments. This study's data sources include interviews, expert validation, student responses, and documentation obtained using Pup-Up Book-based learning media. In this study, data was gathered through interviews and questionnaires. According to the research findings, developing pop-up book learning media included seven research steps: preliminary studies and data collection, planning, initial product development, initial product trials, initial product revisions, field trials, and final product revisions. The level of suitability of the developed learning media is "very good" based on design and material aspects, with an average value of 4,49 and 4,64, as well as product trial results "Very Good" with an average value of 4.68.